Diagnosing Emerging Fungal Threats: A One Health Perspective - Ghosh, Pria N.; Fisher, Matthew C.; Bates, Kieran A. (Frontiers in Genetics, 2018)
Emerging fungal pathogens are a growing threat to global health, ecosystems, food security and the world economy. Over the last century globalisation, changes in climate and land use and the increasing use of immunosuppressive and antimicrobial drugs have enabled endemic pathogens to spread to previously uninfected regions igniting disease outbreaks with sometimes catastrophic effects. In order to tackle contemporary epidemics and predemic threats, there is a pressing need for a unified approach in identification and monitoring of fungal pathogens. In this paper, we discuss current high throughput technologies, as well as new platforms capable of combining diverse data types to inform practical epidemiological strategies with a focus on emerging fungal pathogens of wildlife.